KEARIFAN LOKAL DALAM TATA KELOLA AIR: KAJIAN ETNOEKOLOGI MASYARAKAT ADAT PENGLIPURAN, BANGLI, BALI - Juliasih, Ni Ketut Ayu; I Made Gede Anadhi; I Nyoman Arsana; I Putu Sudiartawan; I Putu Gede Suyoga (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
This article examines the practices of local wisdom in water management by indigenous communities in Penglipuran Village, Bangli, Bali, through an ethnoecological approach. This village is known as one of the traditional villages that still maintains traditional cultural structures and ecological systems in managing natural resources. This research was conducted using a qualitative approach, through participant observation, in-depth interviews, and documentation studies. The findings indicate that water governance in Penglipuran is not merely a technical practice, but rather part of an integrated system of beliefs, social structures, and cultural rituals. It’s deeply rooted in local wisdom structured around the dimensions of cosmos (spiritual and cosmological values), corpus (local ecological knowledge), and praxis (collective action). The water system managed through customary institutions, the preservation of bamboo forests as water catchment areas, and the sacred values of the tirta ritual demonstrate the close relationship between culture and the environment. This study strengthens the idea that local wisdom is a form of adaptive and sustainable ecological knowledge. These findings can contribute to the development of local community-based conservation policies.